(untitled) (Stato, Chiese e pluralismo confessionale, 2012)
Full text, with notes, of the paper presented at the International Conference “ Holy places and religious institutions. Comparative legal and religious approaches – Italy/Balkans, Israel/Palestine Israel”, organized by LUMSA University (Rome) and the Catholic America – Columbus School of Law (Washington) in Rome, LUMSA, December 10-11, 2008: Dec. 10th session on the subject of “Holy places and religious property in Italy ”. It will be published in the conference proceedings. Translated from Italian by Paola Bernardini. INDEX: 1. The issue of redundant places of worship in Europe - 2. Canonical perspectives - 2.1. The regulations according to the Code of Canon Law - 2.2. General criteria for change in churches’ deployment. The Guidelines of the Episcopal Conference of Italy (CEI) about the cultural goods of the Church in Italy (1992) - 2.3. The documents of other episcopates (Germany and Switzerland) – 3. The phenomenon of churches’ desertion in some countries - 3.1. France - 3.2. Québec (Canada) - 3.3. United States of America - 4. The situation in Italy - 4.1. Ownership of the churches - 4.2. Financial aspects - 4.3. Legal protection of the destination bond - 4.4. Churches as cultural heritage - 4.5. Fiscal considerations - 4.6. The recent CEI Directive (2005) - 5. Concluding remarks. Abstract: Nowadays one of the major issues concerning ecclesiastical, or religious, property in Europe, as elsewhere, consists of deciding what to do with redundant churches and places of worship of traditional Christian denominations, all of which have lost their original use, either due to a formal decision of the ecclesiastical authorities or to simple closure to the public. This might have been caused by a series of events, like a significant decrease in the church attendance, limited public resources, new urban planning projects and the fall in religious vocation. For these places there is either the prospect of a new use, or a slow process of decay which can ultimately end up in a sale, or demolition. This problem is faced today with singular urgency in Europe, where it determines an increased risk of decay of much of the historical-artistic heritage, together with the abandonment of the countryside and mountain locations and a progressive desertion of historical town centres. Consequently, the issue concerns not only the religious community but also the civil authorities and public opinion, more and more sensitive to the protection of cultural heritage and the historical memory of local communities. This paper examines many aspects of the issue in some countries (Italy, Germany, Switzerland, France, Québec, the United States), comparing the different legal frameworks and the documents of some national episcopal assemblies on the subject, especially about the change in the use of churches. Finally it concentrates on the situation in Italy, where the legal framework on this subject is strictly connected with the system of church-state relations, making some concluding remarks about future prospects and possible solutions to some of the more serious aspects of the issue.